2011
DOI: 10.4012/dmj.2011-110
|View full text |Cite
|
Sign up to set email alerts
|

A review of the developments of self-etching primers and adhesives —Effects of acidic adhesive monomers and polymerization initiators on bonding to ground, smear layer-covered teeth

Abstract: This paper reviews the developments of self-etching primers and adhesives, with a special focus on the effect of acidic adhesive monomers and polymerization initiators on bonding to ground, smear layer-covered teeth. Ionized acidic adhesive monomers chemically interact with tooth substrates and facilitate good bonding to ground dentin. Polymerization initiators in self-etching primers further promote effective bonding to ground dentin. To promote bonding to both dentin and enamel, phosphonic acid monomers such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…However, it has been reported that the phosphonate ion possesses the capacity to exchange with the PO −3 4 in hydroxyapatite crystals and to bind with the calcium in hydroxyapatite through a chemical reaction [22] that promotes an increase in bond strength to the enamel. [23][24][25] Therefore, it seemed likely that the presence of the 6-MHPA monomer in the primer played an important role in the bonding to the enamel despite the mildness of the demineralization observed in this study. An activator containing carboxylic acid is designed to enhance the bonding ability to primer-pretreated enamel.…”
Section: Discussionmentioning
confidence: 56%
“…However, it has been reported that the phosphonate ion possesses the capacity to exchange with the PO −3 4 in hydroxyapatite crystals and to bind with the calcium in hydroxyapatite through a chemical reaction [22] that promotes an increase in bond strength to the enamel. [23][24][25] Therefore, it seemed likely that the presence of the 6-MHPA monomer in the primer played an important role in the bonding to the enamel despite the mildness of the demineralization observed in this study. An activator containing carboxylic acid is designed to enhance the bonding ability to primer-pretreated enamel.…”
Section: Discussionmentioning
confidence: 56%
“…The structures of the new acidic monomers were confirmed by 1 H NMR, 31 P NMR, 13 C NMR spectroscopy as well as by HRMS. As an example, the 13 C NMR spectrum of monomer 12 is represented on Figure 3.…”
Section: Synthesesmentioning
confidence: 80%
“…1 H NMR, 13 C NMR and 31 P NMR spectra were recorded on a DPX-400 spectrometer using TMS as internal reference for 1 H NMR and 13 C NMR chemical shifts and using H 3 PO 4 (85%) as external reference for 31 P NMR chemical shifts. Data are given in the following order: chemical shift in ppm, multiplicity (s, singlet; d, doublet; t, triplet; q, quadruplet; qt, quintuplet; m, multiplet), coupling constant in Hertz, assignment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations